Carbon material precursor and method for producing carbon material

JP2025035494APending Publication Date: 2025-03-13KK TOYOTA CHUO KENKYUSHO

Patent Information

Application Number
JP2023142560
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0013】 本開示によれば、延伸処理時及び耐炎化処理時の軟化による垂れや融着を抑制でき、延伸処理時及び耐炎化処理時に高い張力を付与できる炭素材料前駆体、及び炭素材料の製造方法が提供され得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025035494000002
    Figure 2025035494000002
  • Figure 2025035494000001
    Figure 2025035494000001
Patent Text Reader

Abstract

To provide a carbon material precursor which resists sagging and fusion due to softening during stretching and flame-retardant treatment, and enables high tension application during the stretching and flame-retardant treatment.SOLUTION: A carbon material precursor of the present disclosure comprises an acrylamide-based copolymer and a cationic metal, wherein the acrylamide-based copolymer comprises at least one structural unit derived from a vinyl monomer having an anionic functional group.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to carbon material precursors and methods for producing carbon materials. [Background technology]

[0002] Carbon fiber is lightweight and has excellent mechanical properties. Therefore, carbon fiber composite materials are attracting attention as a material to replace metal materials. As a method for producing carbon fiber, a method is known in which a fiber bundle obtained by spinning polyacrylonitrile is subjected to a flame retardant treatment and then a carbonization treatment is performed (for example, Patent Document 1 and Patent Document 2).

[0003] On the other hand, acrylamide-based polymers containing acrylamide-based monomers are known as precursors of carbon fibers. Acrylamide-based polymers are water-soluble polymers and are inexpensive when polymerized, spun, and the like. Acrylamide-based polymers can use water, which has a small environmental impact, as a solvent. Therefore, reduction in the manufacturing cost of carbon fibers is expected (for example, Patent Document 3 and Patent Document 4).

[0004] However, when an acrylamide-based polymer is subjected to a heat treatment (e.g., stretching, flame-proofing, carbonization, etc.), it may soften and not maintain the desired shape. In response to this, Patent Document 5 discloses a carbon material precursor composition that is capable of crosslinking an acrylamide-based copolymer and maintaining the desired shape. The carbon material precursor composition contains a carbon material precursor made of a specific acrylamide-based copolymer, at least one additive component selected from the group consisting of acids and their salts, and a compound containing a polyfunctional amino group. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2006-183159 A [Patent Document 2] JP 2008-202208 A [Patent Document 3] JP 2019-26827 A [Patent Document 4] JP 2019-167516 A [Patent Document 5] JP 2019-172800 A Summary of the Invention [Problem to be solved by the invention]

[0006] When a carbon material precursor (e.g., fiber, etc.) made of an acrylamide polymer is stretched in the horizontal direction and subjected to a flame-retardant treatment, the polymer may soften due to heat, causing sagging or fusion between polymers. If sagging occurs, problems such as contact with equipment and deformation of shape may occur. Furthermore, problems such as insufficient tension may be applied during stretching and flame-retardant treatment due to a decrease in storage modulus caused by sagging and softening of the polymer may occur.

[0007] If fusion occurs, the strength and appearance quality of the carbon material may decrease. The stretching and flame-retardant treatments are carried out at temperatures of 160°C or higher. If the heating temperature of the acrylamide-based polymer is increased, the acrylamide-based polymer suddenly softens from about 160°C (i.e., the glass transition temperature Tg of the acrylamide-based polymer). Therefore, fusion between polymers is likely to occur during stretching or flame-retardant treatment in a heated environment. If fusion occurs, the flame-retardant treatment and the subsequent carbonization treatment will not proceed sufficiently, and there is a risk of a decrease in the carbonization yield, a decrease in the strength of the carbon material, and a decrease in the appearance quality.

[0008] As in Patent Document 5, the softening of the carbon material precursor can be suppressed and the carbon material precursor is less likely to sag by crosslinking the polymer with heat during the stretching treatment and the flame-retardant treatment. However, when the carbon material precursor in a fibrous form is bundled and stretched and flame-retardant treatment is performed, there is a risk that the contact portions between the polymers will melt before the crosslinking reaction occurs, causing fusion.

[0009] Therefore, there is a demand for a carbon material precursor that can suppress sagging and fusion due to softening of the polymer even when heated at a temperature exceeding the glass transition temperature Tg (about 160°C) of the acrylamide-based copolymer (i.e., during stretching or flame-proofing), and can impart high tension during stretching and flame-proofing (i.e., has a high storage modulus).

[0010] An object of one embodiment of the present disclosure is to provide a carbon material precursor that can suppress sagging or fusion due to softening during stretching and flame-resistant treatment and can impart high tension during stretching and flame-resistant treatment, and a method for producing a carbon material.

[0011] As a result of intensive research into the above-mentioned problems, the present inventors have found that ionic crosslinks are formed by adding a cationic metal to an acrylamide copolymer having an anionic functional group. This makes it possible to obtain a carbon material precursor that is less likely to sag or melt due to softening during heat treatment at a temperature equal to or higher than the glass transition temperature Tg (about 160°C) of the acrylamide copolymer and has a high storage modulus. The ionic crosslinks are formed at the time the carbon material precursor is molded. Therefore, the present inventors have found that melting is less likely to occur at the contact points between the acrylamide copolymers during stretching and flame-resistant treatment, and melting is suppressed, leading to the completion of the invention.

[0012] Means for solving the above problems include the following embodiments. <1> The present invention includes an acrylamide copolymer and a cationic metal, The carbon material precursor, wherein the acrylamide copolymer contains at least one type of structural unit derived from a vinyl monomer having an anionic functional group. <2> The valence of the cationic metal is divalent or more. <1> The carbon material precursor according to claim 1, <3> The content of the cationic metal is 0.1 parts by mass to 10 parts by mass with respect to 100 parts by mass of the acrylamide copolymer. <1> or <2> The carbon material precursor according to claim 1, <4> The content of the constituent units derived from the vinyl monomer having an anionic functional group is 0.1 mol % to 50 mol % based on the total amount of the constituent units of the acrylamide copolymer. <1> ~ <3> 10. The carbon material precursor according to claim 9, <5> The anionic functional group is a carboxy group. <1> ~ <4> 10. The carbon material precursor according to claim 9, <6> The method further comprises the steps of: <1> ~ <5> 10. The carbon material precursor according to claim 9, <7> The biomass fiber includes fiber derived from at least one selected from the group consisting of cellulose and nitrogen-containing polysaccharide polymers. <6> The carbon material precursor according to claim 1, <8> The above <1> ~ <7> 1. A flame-resistant treatment is performed on the carbon material precursor according to any one of the above items to obtain a flame-resistant product; subjecting the flame-retardant material to a carbonization treatment; A method for producing a carbon material, comprising: Effect of the Invention

[0013] According to the present disclosure, a carbon material precursor that can suppress sagging and fusion due to softening during stretching treatment and flame-stabilizing treatment and can impart high tension during stretching treatment and flame-stabilizing treatment, and a method for producing a carbon material can be provided. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a diagram illustrating the method for evaluating sagging in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] In the present disclosure, a numerical range indicated using "~" includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with the value shown in the synthesis examples. In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved.

[0016] In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple types of substances corresponding to each component are present in the carbon material precursor, the content or amount of each component means the total content or amount of the multiple types of substances present in the carbon material precursor, unless otherwise specified.

[0017] (1) Carbon material precursor The carbon material precursor of the present disclosure includes an acrylamide copolymer and a cationic metal. The acrylamide copolymer includes at least one type of structural unit derived from a vinyl monomer having an anionic functional group (hereinafter, also referred to as an "anionic vinyl monomer").

[0018] The term "carbon material precursor" refers to a raw material for producing a carbon material that has not been subjected to either a flame retardant treatment or a carbonization treatment. The term "acrylamide copolymer" refers to a copolymer of an acrylamide monomer (hereinafter also referred to as "acrylamide monomer") and a monomer other than an acrylamide monomer (hereinafter also referred to as "other polymerizable monomer"). The other polymerizable monomer includes an anionic vinyl monomer. The term "cationic metal" refers to a metal that can form a positive ion (cation) in water. The term "anionic functional group" refers to a functional group capable of forming an anion in the presence of water. Here, the temperature at which the anion is formed in the presence of water is not particularly limited, and the functional group may be capable of forming an anion in the presence of water at a high temperature.

[0019] Since the carbon material precursor of the present disclosure has the above-described configuration, sagging and fusion due to softening during stretching and flame-stabilizing treatment can be suppressed, and high tension can be applied during stretching and flame-stabilizing treatment. This effect is believed to be due to, but not limited to, the following reasons. The carbon material precursor of the present disclosure includes an acrylamide copolymer and a cationic metal. The acrylamide copolymer includes a structural unit derived from an anionic vinyl monomer. As a result, the anionic functional group contained in the acrylamide copolymer forms an ionic bond (i.e., an ionic crosslink) with a cationic cationic metal (e.g., calcium, etc.). Therefore, the heat resistance of the carbon material precursor is improved. As a result, the carbon material precursor of the present disclosure is less likely to sag and melt even when heated at a temperature exceeding the glass transition temperature Tg (about 160°C) of the acrylamide copolymer, and the storage modulus is less likely to decrease. Therefore, it is presumed that the use of the carbon material precursor of the present disclosure can suppress sagging and melting due to softening during stretching and flame-resistant treatment, and can impart high tension during stretching and flame-resistant treatment. In thermal crosslinking, the contact portions between the polymers melt and fuse before the crosslinking reaction occurs at the contact portions between the carbon material precursors during the stretching treatment and the flame-resistant treatment. On the other hand, in ionic crosslinking, crosslinks are formed at the time when the carbon material precursor is molded. As a result, it is presumed that the carbon material precursor of the present disclosure is unlikely to fuse and sag even when heated at a temperature exceeding the glass transition temperature Tg (about 160°C) of the acrylamide-based copolymer. Therefore, when the carbon material precursor of the present disclosure is used, melting is unlikely to occur at the contact portions between the carbon material precursors during the stretching treatment and the flame-resistant treatment, and the occurrence of fusion is suppressed.

[0020] The form of the carbon material precursor of the present disclosure is not particularly limited, and examples thereof include fibers, powders, pellets, lumps, solutions (e.g., aqueous or non-aqueous solutions), suspensions (i.e., slurry liquids), etc. The term "pellets" refers to particles made of a carbon material precursor, and can be obtained, for example, by melting the carbon material precursor in a melt kneading device or the like, discharging it from a nozzle to solidify, and then granulating it with a pelletizer or by pulverization.

[0021] (1.1) Acrylamide copolymer The carbon material precursor of the present disclosure includes an acrylamide-based copolymer.

[0022] An acrylamide copolymer is a copolymer of an acrylamide monomer and another polymerizable monomer, that is, the acrylamide copolymer is composed of a constitutional unit derived from an acrylamide monomer (hereinafter also referred to as an "acrylamide monomer unit") and a constitutional unit derived from another polymerizable monomer (hereinafter also referred to as an "other polymerizable monomer unit").

[0023] The content of the acrylamide monomer units is preferably 30 mol % or more, more preferably 40 mol % or more, even more preferably 50 mol % or more, particularly preferably 55 mol % or more, and most preferably 60 mol % or more, relative to the total amount of the constituent units of the acrylamide copolymer. When the content of the acrylamide monomer unit is 30 mol % or more, the solubility of the acrylamide copolymer in an aqueous solvent or an aqueous mixed solvent tends to be improved. From the viewpoint of suppressing fusion, etc., the content of acrylamide-based monomer units is preferably 99.9 mol % or less, more preferably 99 mol % or less, even more preferably 95 mol % or less, particularly preferably 90 mol % or less, and most preferably 85 mol % or less, relative to the total amount of constituent units of the acrylamide-based copolymer. The content of the acrylamide monomer unit is preferably 30 mol % to 99.9 mol %.

[0024] From the viewpoint of suppressing fusion, etc., the content of other polymerizable monomer units is preferably 0.1 mol % or more, more preferably 1 mol % or more, even more preferably 5 mol % or more, particularly preferably 10 mol % or more, and most preferably 15 mol % or more, relative to the total amount of constituent units of the acrylamide-based copolymer. From the viewpoint of improving the solubility of the acrylamide-based copolymer in an aqueous solvent or an aqueous mixed solvent, the content of other polymerizable monomer units is preferably 70 mol % or less, more preferably 60 mol % or less, even more preferably 50 mol %, particularly preferably 45 mol % or less, and most preferably 40 mol % or less, relative to the total amount of the constituent units of the acrylamide-based copolymer. The content of the other polymerizable monomer units is preferably 0.1 mol % to 70 mol %.

[0025] The composition ratio of the acrylamide copolymer is: 13 It can be measured by C-NMR, infrared absorption spectroscopy (IR), etc.

[0026] The weight average molecular weight of the acrylamide copolymer is not particularly limited and is usually 5 million or less. From the viewpoint of the production and processability of the carbon material precursor, however, it is preferably 2 million or less, more preferably 1 million or less, even more preferably 500,000 or less, particularly preferably 200,000 or less, even more preferably 130,000 or less, and most preferably 100,000 or less. The weight average molecular weight of the acrylamide copolymer is not particularly limited, but is usually 10,000 or more. From the viewpoint of the strength of the carbon material precursor and the carbon fiber, it is preferably 20,000 or more, more preferably 30,000 or more, and particularly preferably 40,000 or more.

[0027] In the present disclosure, the weight average molecular weight is measured by gel permeation chromatography under the following conditions. The measurement device may be "HLC-8220GPC" manufactured by Tosoh Corporation or a device equivalent thereto. (Measurement conditions) Column: TSKgel GMPWXL x 2 + TSKgel G2500PWXL x 1 Eluent: 100 mM sodium nitrate aqueous solution / acetonitrile (=80 / 20 (volume ratio)) ·Eluent flow rate: 1.0ml / min Column temperature: 40℃ Molecular weight standards: Standard polyethylene oxide / Standard polyethylene glycol Detector: Refractive index detector

[0028] (1.1.1) Acrylamide monomers Examples of acrylamide monomers include acrylamide, ethacrylamide, crotonamide, itaconic acid diamide, cinnamic acid amide, maleic acid diamide, N-alkyl acrylamides such as N-methyl acrylamide, N-ethyl acrylamide, Nn-propyl acrylamide, N-isopropyl acrylamide, Nn-butyl acrylamide, and N-tert-butyl acrylamide, N-cycloalkyl acrylamides such as N-cyclohexyl acrylamide, dialkyl acrylamides such as N,N'-dimethyl acrylamide, dialkyl amino alkyl acrylamides such as dimethyl amino ethyl acrylamide and dimethyl amino propyl acrylamide, hydroxy alkyl acrylamides such as N-(hydroxy methyl) acrylamide and N-(hydroxy ethyl) acrylamide, N-aryl acrylamides such as N-phenyl acrylamide, diacetone acrylamide, and N,N'-methylene bisacrylamide, etc. N-alkylenebisacrylamides; methacrylamide; N-alkyl methacrylamides such as N-methyl methacrylamide, N-ethyl methacrylamide, Nn-propyl methacrylamide, N-isopropyl methacrylamide, N-n-butyl methacrylamide, and N-tert-butyl methacrylamide; N-cycloalkyl methacrylamides such as N-cyclohexyl methacrylamide; dialkyl methacrylamides such as N,N-dimethyl methacrylamide; dialkylaminoalkyl methacrylamides such as dimethylaminoethyl methacrylamide and dimethylaminopropyl methacrylamide; hydroxyalkyl methacrylamides such as N-(hydroxymethyl) methacrylamide and N-(hydroxyethyl) methacrylamide; N-aryl methacrylamides such as N-phenyl methacrylamide; diacetone methacrylamide; and N,N'-alkylene bismethacrylamides such as N,N'-methylene bismethacrylamide. From the viewpoint of the solubility of the acrylamide-based copolymer in an aqueous solvent or an aqueous mixed solvent, among the above acrylamide-based monomers, acrylamide, N-alkylacrylamide, dialkylacrylamide, methacrylamide, N-alkyl methacrylamide or dialkyl methacrylamide is preferred, and acrylamide is more preferred. The acrylamide monomers may be used alone or in combination of two or more.

[0029] (1.1.2) Other polymerizable monomers Other polymerizable monomers include vinyl monomers having anionic functional groups.

[0030] (1.1.2.1) Anionic vinyl monomers The anionic vinyl monomer has an anionic functional group, such as a carboxy group, a sulfo group, a phosphate group (phosphate groups include phosphonic acid groups, phosphorous acid groups, phosphinic acid groups, phosphinic acid groups, etc.), a nitro group, or a phenolic hydroxyl group. Examples of the anionic vinyl monomer include unsaturated carboxylic acid and its salt, sulfonic acid vinyl monomer and its salt, phosphoric acid vinyl monomer and its salt, nitric acid vinyl monomer and its salt, phenolic vinyl monomer and its salt, etc. The unsaturated carboxylic acid also includes unsaturated carboxylic acid precursors that form unsaturated carboxylic acid, such as unsaturated carboxylic acid anhydrides that form unsaturated carboxylic acid in the presence of water, and unsaturated carboxylic acid esters (e.g., tert-butyl esters) that form unsaturated carboxylic acid at high temperatures and / or in the presence of acid. Examples of the unsaturated carboxylic acid include acrylic acid, methacrylic acid, maleic acid and its derivatives (e.g., maleic acid monoester, etc.), fumaric acid and its derivatives (e.g., fumaric acid monoester, etc.), itaconic acid and its derivatives (e.g., itaconic acid monoester, etc.), citraconic acid and its derivatives (e.g., citraconic acid monoester, etc.), mesaconic acid and its derivatives (e.g., mesaconic acid monoester, etc.), crotonic acid, isocrotonic acid, etc. Examples of the salts of the unsaturated carboxylic acid include metal salts (e.g., sodium salts, potassium salts, calcium salts, etc.), ammonium salts, amine salts, etc. of the unsaturated carboxylic acid. Examples of the unsaturated carboxylic acid precursor include maleic anhydride, itaconic anhydride, citraconic anhydride, acrylic acid esters (for example, tert-butyl acrylate, etc.), and methacrylic acid esters (for example, tert-butyl methacrylate, etc.). Examples of sulfonic acid vinyl monomers include acrylamido tertiary butyl sulfonic acid, vinyl sulfonic acid, vinylbenzene sulfonic acid, 2-acrylamido-2-methylpropane sulfonic acid, styrene sulfonic acid, isoprene sulfonic acid, allyl sulfonic acid, methacrylic sulfonic acid, etc. Examples of salts of sulfonic acid vinyl monomers include metal salts (e.g., sodium salts, potassium salts, calcium salts, etc.), ammonium salts, amine salts, etc. of sulfonic acid vinyl monomers. Examples of the phosphoric acid vinyl monomer include vinyl phosphoric acid, 2-acryloyloxyethyl acid phosphate, 2-methacryloyloxyethyl acid phosphate, 2-methacryloyloxyethyl acid phosphate, vinyl phosphonic acid, vinyl phosphorous acid, vinyl phosphinic acid, phenylvinylphosphinic acid, vinyl phosphinic acid, etc. Examples of the salts of the phosphoric acid vinyl monomer include metal salts (e.g., sodium salts, potassium salts, calcium salts, etc.), ammonium salts, amine salts, etc. of the phosphoric acid vinyl monomer. Examples of the nitric acid vinyl monomer include vinyl nitrate, 2-nitrovinylbenzene, etc. Examples of the salts of the nitric acid vinyl monomer include metal salts (e.g., sodium salts, potassium salts, calcium salts, etc.), ammonium salts, amine salts, etc. of the nitric acid vinyl monomer. Examples of the phenolic vinyl monomer include 2-vinylphenol, 4-vinylphenol, etc. Examples of the salts of the phenolic vinyl monomer include metal salts (e.g., sodium salts, potassium salts, calcium salts, etc.), ammonium salts, amine salts, etc. of the phenolic vinyl monomer. The anionic vinyl monomers may be used alone or in combination of two or more.

[0031] Among the above anionic vinyl monomers, from the viewpoint of polymerizability with the acrylamide copolymer, unsaturated carboxylic acids and salts thereof are preferred, and acrylic acid, maleic acid, fumaric acid or itaconic acid is more preferred. Among the above anionic vinyl monomers, from the viewpoint of suppressing fusion, unsaturated carboxylic acids are preferred, and acrylic acid, maleic acid, fumaric acid and itaconic acid are more preferred.

[0032] The content of the structural unit derived from an anionic vinyl monomer (hereinafter also referred to as "anionic vinyl monomer unit") is preferably 0.1 mol% to 70 mol% based on the total amount of the structural units of the acrylamide copolymer, which allows the formation of ionic crosslinks and improvement of heat resistance while maintaining the solubility of the acrylamide copolymer in aqueous solvents or aqueous mixed solvents. From the viewpoints of the formability of ionic crosslinks, suppression of fusion, and promotion of flame retardant reaction, the content of the anionic vinyl monomer unit is more preferably 0.5 mol% or more, even more preferably 1 mol% or more, particularly preferably 2 mol% or more, and most preferably 3 mol% or more. From the viewpoint of improving the solubility of the acrylamide copolymer in an aqueous solvent or an aqueous mixed solvent, the content of the anionic vinyl monomer unit is more preferably 50 mol % or less, even more preferably 35 mol % or less, particularly preferably 20 mol % or less, and most preferably 10 mol % or less.

[0033] (1.1.2.2) Vinyl monomers without anionic functional groups The other polymerizable monomers may include, in addition to the anionic vinyl monomer, a vinyl monomer not having an anionic functional group (hereinafter also referred to as a "non-anionic vinyl monomer").

[0034] Examples of the non-anionic vinyl monomer include vinyl cyanide monomers, aromatic vinyl monomers, vinyl halide monomers, vinyl alcohol monomers, vinyl carboxylate monomers, and olefin monomers.

[0035] Examples of the vinyl cyanide monomer include acrylonitrile, methacrylonitrile, 2-hydroxyethyl acrylonitrile, chloroacrylonitrile, chloromethyl acrylonitrile, ethoxyacrylonitrile, and vinylidene cyanide.

[0036] Examples of the aromatic vinyl monomer include styrene and α-methylstyrene. Examples of the vinyl halide monomer include vinyl chloride. The vinyl alcohol monomer includes vinyl alcohol. Examples of the vinyl carboxylate monomer include vinyl acetate and vinyl propionate. Examples of the olefin monomer include ethylene, propylene, isopropylene, and butadiene. The non-anionic vinyl monomers may be used alone or in combination of two or more kinds.

[0037] The content of structural units derived from non-anionic vinyl monomers among other polymerizable monomers may be 0 mol% relative to the total amount of structural units of the acrylamide copolymer, but when structural units derived from non-anionic vinyl monomers are contained, the content of structural units derived from non-anionic vinyl monomers is preferably 0.1 mol% to 69.9 mol%, more preferably 1 mol% to 69.5 mol%, even more preferably 2 mol% to 69 mol%, even more preferably 3 mol% to 49.9 mol%, particularly preferably 5 mol% to 49 mol%, and most preferably 15 mol% to 47 mol%, relative to the total amount of structural units of the acrylamide copolymer.

[0038] (1.1.3) Synthesis of acrylamide copolymers The acrylamide copolymer may be one synthesized by a conventionally known method. The synthesis of the acrylamide copolymer can be carried out by utilizing known polymerization reactions such as radical polymerization, cationic polymerization, anionic polymerization, living radical polymerization, etc. Among the above polymerization reactions, radical polymerization is preferred from the viewpoint of reducing synthesis costs. The synthesis of the acrylamide copolymer can be carried out by utilizing a polymerization method such as solution polymerization, suspension polymerization, precipitation polymerization, dispersion polymerization, or emulsion polymerization (for example, inverse phase emulsion polymerization). When synthesizing an acrylamide-based copolymer by solution polymerization, it is preferable to use a solvent in which the raw material monomers and the resulting acrylamide-based copolymer are soluble. From the viewpoint of low-cost and safe synthesis, it is more preferable to use an aqueous solvent or an aqueous mixed solvent, and it is even more preferable to use an aqueous solvent. Examples of the aqueous solvent include water, alcohol, and a mixture thereof, with water being particularly preferred. The aqueous mixed solvent means a mixed solvent of the above aqueous solvent and an organic solvent, and examples of the organic solvent include tetrahydrofuran, dimethylsulfoxide, and dimethylformamide.

[0039] In the synthesis of the acrylamide copolymer by radical polymerization, it is preferable to use a polymerization initiator. As the polymerization initiator, a conventionally known radical polymerization initiator such as azobisisobutyronitrile, benzoyl peroxide, 4,4'-azobis(4-cyanovaleric acid), ammonium persulfate, potassium persulfate, etc. can be used. When an aqueous solvent or an aqueous mixed solvent is used as the solvent, a radical polymerization initiator soluble in the aqueous solvent or the aqueous mixed solvent, such as 4,4'-azobis(4-cyanovaleric acid), ammonium persulfate, or potassium persulfate, is preferred. From the viewpoint of controlling the molecular weight of the acrylamide-based copolymer, it is preferable to use at least one of a polymerization accelerator and a molecular weight regulator in place of or together with the polymerization initiator, and it is more preferable to use a polymerization initiator and a polymerization accelerator in combination. The polymerization accelerator may, for example, be tetramethylethylenediamine. The molecular weight regulator may, for example, be an alkyl mercaptan compound such as n-dodecyl mercaptan. It is particularly preferable to use ammonium persulfate as a polymerization initiator in combination with tetramethylethylenediamine as a polymerization promoter.

[0040] The temperature of the polymerization reaction is not particularly limited, but from the viewpoint of controlling the molecular weight of the acrylamide copolymer, it is preferably 35° C. or higher, more preferably 40° C. or higher, even more preferably 50° C. or higher, particularly preferably 70° C. or higher, and most preferably 75° C. or higher. The upper limit of the polymerization reaction temperature is not particularly limited, and can be 200° C. or lower.

[0041] (1.2) Cationic metals The carbon material precursor of the present disclosure contains a cationic metal. The cationic metal may be used alone or in combination of two or more kinds.

[0042] The valence of the cationic metal is not particularly limited, and examples thereof include monovalent, divalent, trivalent, tetravalent, and pentavalent.

[0043] Examples of monovalent cationic metals include Li, Na, K, Rb, Cs, Ag, and Fr. Examples of divalent cationic metals include Be, Mg, Ca, Sr, Ba, Ra, Co, Mn, Ni, Pd, Zn, and Cu. Examples of trivalent cationic metals include Al, Ga, In, Ti, Fe, La, Cr, Sb, and Ce. Examples of tetravalent cationic metals include Ti, Zr, Hf, Ge, and Sn. An example of the pentavalent cationic metal is Sb.

[0044] The valence of the cationic metal is preferably 2 or more. This makes it easier for the cationic metal to form ionic crosslinks with the anionic functional groups contained in the acrylamide copolymer than when the valence of the cationic metal is 1. As a result, even if the carbon material precursor is heated to a temperature exceeding the glass transition temperature Tg (about 160°C) of the acrylamide copolymer, the storage modulus is unlikely to decrease and sagging and fusion are unlikely to occur. From the viewpoints of the extensibility of the ionically crosslinked acrylamide copolymer and the solubility in an aqueous solvent or an aqueous mixed solvent, the valence of the cationic metal is more preferably from divalent to tetravalent, even more preferably from divalent to trivalent, and particularly preferably divalent.

[0045] Among these, from the viewpoint of the formability of ionic crosslinking, the cationic metal preferably includes an alkaline earth metal (Be, Mg, Ca, Sr, Ba, Ra), more preferably includes Mg, Ca, Sr, Ba, even more preferably includes Mg, Ca, Sr, particularly preferably Ca, Sr, and most preferably Ca.

[0046] The cationic metal may be derived from an inorganic salt or an organic salt. Examples of the inorganic salt include chlorides, hydroxides, carbonates, nitrates, sulfates, phosphates, tungstates, vanadates, molybdates, niobates, borates, and hydrates thereof of cationic metals. Examples of the organic salt include phenols, carboxylates (e.g., acetates, lactates, formates, oxalates, propionates, benzoates, succinates, adipates, etc.), benzenesulfonates, and hydrates thereof of cationic metals.

[0047] The content of the cationic metal is not particularly limited, but is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the acrylamide copolymer, which allows the formation of ionic crosslinks and improvement of heat resistance while maintaining the solubility of the acrylamide copolymer in aqueous solvents or aqueous mixed solvents. The content of the cationic metal is more preferably 0.3 parts by mass or more, even more preferably 0.5 parts by mass or more, and particularly preferably 0.6 parts by mass or more, from the viewpoints of the formability of ionic crosslinks, suppression of fusion, etc. The content of the cationic metal is more preferably 8 parts by mass or less, even more preferably 6 parts by mass or less, and particularly preferably 4 parts by mass or less, from the viewpoints of the solubility of the acrylamide copolymer in an aqueous solvent or aqueous mixed solvent, and the strength of the carbon fiber.

[0048] (1.3) Biomass Fiber The carbon material precursor of the present disclosure preferably further includes a biomass fiber in addition to the acrylamide copolymer and the cationic metal. The biomass fiber interacts with both the acrylamide copolymer and the cationic metal. As a result, the heat resistance of the carbon material precursor is improved.

[0049] Biomass fiber is a fiber derived from a biological resource. There is no particular limitation on the biological resource, and examples thereof include cellulose (cellulose includes lignocellulose containing lignin or hemicellulose, modified cellulose, etc.), nitrogen-containing polysaccharide polymers (e.g., chitin, chitosan, etc.), and proteins (e.g., silk, spider silk, artificial proteins produced by microbial fermentation, etc.). Modified cellulose refers to cellulose in which all or part of the hydroxyl groups have been modified by chemical modification to functional groups that are easily ionized. Examples of functional groups that are easily ionized include functional groups containing a carboxyl group (e.g., a carboxyl group, a carboxymethyl group, etc.), a hydroxyethyl group, a phosphoric acid group, a polyphosphoric acid group, a functional group containing a sulfonic acid group (e.g., a sulfonic acid group, a benzenesulfonic acid group, etc.), and salts thereof. From the viewpoints of affinity with acrylamide copolymers, heat resistance, reinforcing properties, carbonization yield, shape stability, etc., it is preferable that the biomass fiber contains at least one fiber selected from the group consisting of cellulose and nitrogen-containing polysaccharide polymers (e.g., chitin, chitosan, etc.). Chitosan has a structure almost identical to that of chitin, with the amide groups of chitin replaced by amino groups. Therefore, biomass fibers derived from chitin and chitosan have the same properties (e.g., affinity with acrylamide copolymers, heat resistance, reinforcing properties, carbonization yield, shape stability, etc.). The biomass fibers may be used alone or in combination of two or more kinds.

[0050] Biomass fibers can be produced by various production methods, and a preferred example of the production method is defibration of biological resources. Preferred examples of the defibration method include mechanical methods, chemical methods, and methods that combine these. Among these, biomass fibers produced by defibration using a mechanical method, or a combination of defibration using a mechanical method and defibration using a chemical method, are preferred.

[0051] Examples of defibration by mechanical methods include a method of defibrating a biological resource using a machine (e.g., a water jet, a high-pressure homogenizer, a grinder, an impact crusher, a bead mill, etc.). It is also preferable to use a biological resource used for defibration that has been cut to a predetermined length using a beating machine (e.g., a beater, a refiner, etc.).

[0052] When defibration by a mechanical method and defibration by a chemical method are used in combination, at least one of the biological resource and the biomass fiber can be subjected to chemical treatment at one or more of the following timings: before defibration by a mechanical method, during defibration, and after defibration. By chemically modifying at least one of the biological resource and the biomass fiber by chemical treatment and then defibration by a mechanical method, the biological resource can be further refined. Examples of defibration by chemical methods include a method in which all or part of the hydroxyl groups on the surface of the biomass fiber are modified to easily ionized functional groups (e.g., carboxy groups, phosphate groups, etc.) by chemical treatment (e.g., TEMPO oxidation treatment using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), oxidation treatment using sodium hypochlorite, phosphate esterification treatment, sulfate esterification treatment, etc.), thereby making it easier to pulverize the biomass fibers by utilizing the electrostatic repulsion between the biomass fibers. Examples of functional groups that are easily ionized include functional groups containing a carboxy group (e.g., carboxy groups, carboxymethyl groups, etc.), phosphate groups, polyphosphate groups, functional groups containing a sulfonic acid group (e.g., sulfonic acid groups, benzenesulfonic acid groups, etc.), and salts thereof (e.g., metal salts, ammonium salts, amine salts, etc.).

[0053] From the viewpoints of dispersibility in an acrylamide copolymer, heat resistance, reinforcing properties, carbonization yield, etc., the fiber diameter of the biomass fiber is preferably in the range of 1 nm to 100 μm, more preferably in the range of 2 nm to 50 μm, and even more preferably in the range of 3 nm to 20 μm.

[0054] The fiber diameter of the biomass fibers contained in the carbon material precursor is preferably in the range of 1 nm to 100 μm, more preferably in the range of 2 nm to 50 μm, and even more preferably in the range of 3 nm to 20 μm, from the viewpoints of heat resistance, reinforcing property, carbonization yield, and the like.

[0055] The average fiber length of the biomass fibers is not particularly limited, but is preferably in the range of 0.5 μm to 500 μm, and more preferably in the range of 1 μm to 200 μm.

[0056] The average fiber length of the biomass fibers contained in the carbon material precursor is not particularly limited, but is preferably in the range of 0.5 μm to 500 μm, and more preferably in the range of 1 μm to 200 μm.

[0057] The fiber diameter and average fiber length of the biomass fibers can be measured using a microscope, a transmission electron microscope (TEM), a scanning electron microscope (SEM), a scanning probe microscope (SPM), or the like.

[0058] When the biomass fiber is derived from cellulose and nitrogen-containing polysaccharide polymers (e.g., chitin, chitosan, etc.), the degree of polymerization is not particularly limited, but from the viewpoints of heat resistance, reinforcing properties, carbonization yield, shape stability, and handleability of the composition for producing a carbon material precursor, it is preferably 50 to 10,000, more preferably 75 to 5,000, and even more preferably 100 to 2,000.

[0059] The degree of polymerization of cellulose and nitrogen-containing polysaccharide polymers (e.g., chitin, chitosan, etc.) is the number of glucose units, which are the smallest structural units, linked together, and is proportional to the fiber length of the biomass fiber. The degree of polymerization is determined by a viscosity method using a copper ethylenediamine solution. Specifically, 30 g of a suspension in which biomass fiber is diluted with ion-exchanged water to a content of 2±0.3% by mass is dispensed into a centrifuge tube and left to freeze overnight in a freezer. The suspension is then dried in a freeze dryer for 5 days or more, and then heated in a constant temperature dryer set at 105°C for 3 to 4 hours to obtain bone-dry biomass fiber. To measure the reference, 15 ml of pure water and 15 ml of 1 mol / L copper ethylenediamine are added to an empty 50 ml screw tube to prepare a 0.5 mol / L copper ethylenediamine solution. 10 ml of the above 0.5 mol / L copper ethylenediamine solution is placed in a Cannon-Fenske viscometer, left for 5 minutes, and the drop time at 25°C is measured to determine the solvent drop time. Next, to measure the viscosity of the biomass fiber, 0.14g to 0.16g of bone-dry biomass fiber is weighed into an empty 50ml screw tube and 15ml of pure water is added. 15ml of 1mol / L copper ethylenediamine is then added and stirred for 10 minutes at 1000rpm in a planetary super mixer to obtain a 0.5mol / L copper ethylenediamine solution in which the biomass fiber is dissolved. As in the reference measurement, 10ml of the prepared 0.5mol / L copper ethylenediamine solution is placed in a Cannon-Fenske viscometer and left for 5 minutes, after which the fall time at 25°C is measured. The fall time is measured three times and the average value is taken as the fall time of the biomass fiber solution. The degree of polymerization is calculated using the following formula from the mass of the bone-dry biomass fiber used in the measurement, the solvent dripping time, and the biomass fiber solution dripping time. Note that if the degree of polymerization is measured twice or more, the average value is used.

[0060] Mass of biomass fiber in an absolute dry state used in the measurement: a (g) (where a is 0.14 to 0.16) Cellulose concentration in solution: c = a / 30 (g / mL) Solvent drop time: t 0 (sec) Biomass fiber solution drop time: t (sec) Relative viscosity of the solution: η rel =t / t 0 Specific viscosity of the solution: η sp = η rel -1 ·Intrinsic viscosity:[η]=η sp / c(1+0.28η sp ) ·Polymerization degree: DP=[η] / 0.57

[0061] In the present disclosure, homemade or commercially available biomass fibers may be used. Examples of commercially available biomass fibers include RMa-10002, RMa-10005, IMa-10002, IMa-10005, BMa-10002, BMa-10005, BMa-10010, WFo-10002, WFo-10005, WFo-10010, AFo-10002, AFo-10005, AFo-10010, FMa-10002, FMa-10005, FMa-10010, WFo-UNDP, FMa-UNDP, CMF-05DP, and TFo- 10002, TFo-10005, SFo-20002, SFo-20005, SFo-20010, EFo-08002, EFo-08005, EFo-08010 and KCo-30005, PC110T, PC110A, PC100B, Roka Meijin, PC110S, FD100F, FD100G, FD200L, KY100S and KY100G manufactured by Daicel Miraize Ltd., nanoforest-S and nanoforest-M manufactured by Chuetsu Pulp Co., Ltd., T-OP 100 manufactured by Toa Gosei Co., Ltd., I-2SX, C-2SP, I-2AX and I-2SXS manufactured by Daiichi Kogyo Seiyaku Co., Ltd., and ELLEX-S and ELLEX-P manufactured by Daio Paper Co., Ltd.

[0062] From the viewpoint of suppressing fusion and sagging during stretching or flame-resistant treatment, the content of the biomass fiber is preferably 0.1 mass% or more, more preferably 0.5 mass% or more, and even more preferably 0.75 mass% or more, based on the content of the acrylamide-based copolymer. From the viewpoint of manufacturability of the composition for producing a carbon material precursor, the content is preferably 40 mass% or less, more preferably 20 mass% or less, and even more preferably 15 mass% or less.

[0063] (1.4) Other polymers The carbon material precursor of the present disclosure may further contain, in addition to the acrylamide-based copolymer and the cationic metal, another polymer different from the acrylamide-based copolymer.

[0064] From the viewpoints of fusion inhibition, water resistance, and the like, the content of the acrylamide-based copolymer relative to the total mass of the polymer in the carbon material precursor is preferably 50 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, particularly preferably 95 mass% or more, even more preferably 99 mass% or more, and most preferably 100 mass%.

[0065] The other polymer is not particularly limited, but is preferably a polymer that dissolves or disperses in an aqueous solvent or an aqueous mixed solvent, more preferably a polymer that dissolves in an aqueous solvent or an aqueous mixed solvent, and even more preferably a water-soluble polymer. Preferred examples of the other polymer include a polymer obtained by (co)polymerizing at least one of a group consisting of specific monomers, and a hydrophilic polysaccharide polymer (acetyl cellulose, xanthan gum, etc.). Specific monomers include, for example, unsaturated carboxylic acids (e.g., acrylic acid, methacrylic acid, etc.) and salts thereof, unsaturated carboxylic acid esters (e.g., methyl acrylate, etc.), vinyl carboxylates (e.g., vinyl alcohol, vinyl acetate, etc.), vinylpyrrolidone, vinyl sulfonic acid and salts thereof, vinyl sulfonic acid esters (e.g., methyl vinyl sulfonate, etc.), vinylbenzenesulfonic acid and salts thereof, vinylbenzenesulfonic acid esters, carboxyvinyl, polyalkylene glycols (e.g., ethylene glycol, propylene glycol, etc.), unsaturated carboxylic acid anhydrides (e.g., maleic anhydride, etc.), unsaturated dicarboxylic acids (e.g., maleic acid, fumaric acid, etc.) and salts thereof, unsaturated dicarboxylic acid esters (e.g., monomethyl maleate, dimethyl maleate, etc.), 2-acrylamido-2-methylpropanesulfonic acid and salts thereof, 2-acrylamido-2-methylpropanesulfonic acid esters, and the like.

[0066] (1.5)Additional ingredients The carbon material precursor of the present disclosure may further contain an additive component in addition to the acrylamide-based copolymer and the cationic metal.

[0067] Examples of additives include organic solvents, surfactants, crosslinking agents, flame retardant accelerators (for example, a group consisting of acids and their salts), various fillers such as glass fibers, carbon black, carbon nanotubes, and graphene, dispersants, smoothing agents, moisture absorbents, viscosity modifiers, plasticizers, release agents, spreading agents, antioxidants, antibacterial agents, preservatives, rust inhibitors, pH adjusters, etc. The content of the additives can be appropriately adjusted.

[0068] When the carbon material precursor contains the flame retardant accelerator, the formation of a cyclic structure due to a dehydration reaction, a deammonia reaction, etc. is accelerated during flame retardant treatment, and the fusion suppression, the carbonization yield, the strength, and the shape stability of the carbon material tend to be further improved. Note that at least a part of the flame retardant component and its residue may remain in the carbon material.

[0069] Examples of the flame retardant accelerator include inorganic acids such as phosphoric acid, polyphosphoric acid, boric acid, sulfuric acid, nitric acid, and carbonic acid, and organic acids such as oxalic acid, citric acid, and sulfonic acid. Ammonium salts and amine salts of these acids are also included. Among the above, from the viewpoints of fusion inhibition, carbonization yield, and strength and shape stability of the carbon material, the flame retardation accelerator is preferably phosphoric acid, polyphosphoric acid, boric acid, sulfuric acid, or an ammonium salt thereof, more preferably phosphoric acid, polyphosphoric acid, boric acid, or an ammonium salt thereof, and still more preferably phosphoric acid, polyphosphoric acid, an ammonium salt of phosphoric acid, or an ammonium salt of polyphosphoric acid.

[0070] From the viewpoints of fusion inhibition, carbonization yield, and strength and shape stability of the carbon material, the content of the flame retardant accelerator is preferably 0.1 parts by mass to 100 parts by mass, more preferably 0.2 parts by mass to 50 parts by mass, even more preferably 0.5 parts by mass to 30 parts by mass, and particularly preferably 1 part by mass to 20 parts by mass, relative to 100 parts by mass of the acrylamide-based copolymer.

[0071] A conventionally known oil such as a silicone-based oil may be applied to the surface of the carbon material precursor of the present disclosure from the viewpoint of suppressing fusion. When the carbon material precursor of the present disclosure is in a fibrous form, a conventionally known oil such as a silicone-based oil may be applied to the surface from the viewpoint of improving bundling and suppressing fusion between fibers. The amount of the oil applied is not particularly limited, but is preferably 0.1 to 20 parts by mass, and more preferably 1 to 10 parts by mass, relative to 100 parts by mass of the acrylamide copolymer.

[0072] (1.6) Solvent The carbon material precursor of the present disclosure may further contain a solvent in addition to the acrylamide-based copolymer and the cationic metal.

[0073] Examples of the solvent include aqueous solvents (e.g., water, alcohol, and mixed solvents thereof), aqueous mixed solvents (mixed solvents of the aqueous solvents and organic solvents (e.g., tetrahydrofuran)), and the like, and it is preferable that the solvent contains water. The solvent may be used alone or in combination of two or more kinds. From the viewpoint of reducing production costs and reducing environmental impact, the content of water relative to the total amount of solvent is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, particularly preferably 99 mass% or more, and may be 100 mass%.

[0074] The solvent content in the carbon material precursor can be appropriately adjusted from the viewpoints of coating, spinning, and the like, and from the viewpoint of manufacturability, it is preferably 5% to 99%, more preferably 10% to 95%, and even more preferably 25% to 90%.

[0075] (1.7) Method for producing carbon material precursor Examples of the method for producing the carbon material precursor include a first production method, a second production method, and a third production method. The first production method is a method for obtaining a carbon material precursor by dissolving and mixing an inorganic salt of a cationic metal in an aqueous solvent or aqueous mixed solvent in which an acrylamide copolymer has been dissolved, and then drying the resulting mixture. The second production method is a method for obtaining a carbon material precursor by dissolving and mixing an acrylamide copolymer in an aqueous solvent or aqueous mixed solvent in which an inorganic salt of a cationic metal has been dissolved, and then drying the resulting mixture. The third production method is a method for obtaining a carbon material precursor by dissolving an acrylamide copolymer obtained by copolymerizing a cationic metal salt among anionic vinyl monomers in an aqueous solvent or aqueous mixed solvent, and drying the resulting solution.

[0076] (2) Manufacturing method of carbon material The method for producing a carbon material according to the present disclosure includes subjecting a carbon material precursor according to the present disclosure to a flame-resistant treatment to obtain a flame-resistant material (hereinafter also referred to as a "flame-resistant treatment step"), and subjecting the flame-resistant material to a carbonization treatment (hereinafter referred to as a "carbonization treatment step"), thereby obtaining a carbon material having excellent strength. Use of the carbon material precursor according to the present disclosure suppresses fusion and sagging due to softening of the carbon material precursor during stretching and flame-resistant treatment, and allows the carbon material precursor to be imparted with high tension.

[0077] The term "flameproofing treatment" refers to subjecting a carbon material precursor to a heat treatment in an oxidizing gas atmosphere. The term "carbonization treatment" refers to a treatment for carbonizing a flame-resistant carbon material precursor. More specifically, the term "carbonization treatment" refers to a treatment for heat-treating a flame-resistant carbon material precursor in a low-oxygen atmosphere (preferably an environment in which oxygen is blocked).

[0078] (2.1) Flameproofing treatment process In the flame-resistant treatment step, the carbon material precursor of the present disclosure is subjected to a flame-resistant treatment to obtain a flame-resistant material.

[0079] The temperature of the flame retardant treatment is not particularly limited, but is preferably 150°C to 500°C, more preferably 175°C to 450°C, and further preferably 200°C to 420°C. The temperature of the flame-resistant treatment includes not only the maximum temperature during the flame-resistant treatment (hereinafter also referred to as the "flame-resistant treatment temperature") but also the temperature during the temperature rise process up to the flame-resistant treatment temperature.

[0080] The maximum temperature during the flame retardant treatment is preferably 200°C to 500°C, more preferably 250°C to 450°C, further preferably 305°C to 440°C, particularly preferably 310°C to 430°C, and most preferably 315°C to 420°C. By setting the flame-retardant treatment temperature to 250° C. or higher, the heat resistance and carbonization yield of the flame-retardant material tend to be improved. By setting the flame-retardant treatment temperature at 500° C. or less, thermal decomposition of the flame-retardant material tends to be suppressed.

[0081] In the flame-retardant treatment of the carbon material precursor, it is preferable to subject the carbon material precursor to a stretching treatment. By subjecting the carbon material precursor to a stretching treatment, the acrylamide copolymer contained in the carbon material precursor is oriented, and the tensile strength of the flame-retardant and the tensile strength after carbonization tend to be improved. The stretching treatment is preferably carried out at least during heating at the flame-proofing treatment temperature. From the viewpoint of improving the tensile strength of the flame-resistant product, it is preferable to carry out a stretching treatment also during the temperature rise process up to the flame-resistant treatment temperature. The stretching treatment may be carried out from the beginning or during the temperature rise process. The stretching treatment may be carried out while controlling the moisture absorption rate during the spinning treatment or in a step prior to the flame retardant treatment.

[0082] The tension applied to the carbon material precursor during the stretching process is not particularly limited, but in the case of a fiber shape, it is preferably 0.05 mN / tex to 2000 mN / tex, more preferably 0.1 mN / tex to 500 mN / tex, even more preferably 0.1 mN / tex to 200 mN / tex, and particularly preferably 0.2 mN / tex to 100 mN / tex. By setting the tension applied to the carbon material precursor during the stretching process within the above numerical range, it is possible to improve the fusion suppression property and to suppress the occurrence of breakage and fluff in the flame-resistant material.

[0083] In the present disclosure, the tension (unit: mN / tex) applied to a fibrous carbon material precursor refers to the tension (unit: mN) applied to the carbon material precursor during flame retardant treatment divided by the fineness (unit: tex) of the carbon material precursor in an absolute dry state. In other words, the tension applied to a fibrous carbon material precursor is the tension per unit fineness of the carbon material precursor. The tension can be adjusted by adjusting the speed at the inlet and outlet of a heating device such as a flame-proofing furnace, or by using a load cell, a spring, a weight, an air cylinder, or the like.

[0084] The flame retardant treatment time (i.e., heating time at the flame retardant treatment temperature) is not particularly limited, but from the viewpoints of carbonization yield and production costs, it is preferably 1 to 120 minutes, more preferably 2 to 60 minutes, even more preferably 3 to 50 minutes, and particularly preferably 4 to 40 minutes. The flameproofing treatment time may be more than 2 hours.

[0085] The carbon material precursor of the present disclosure may be subjected to a crosslinking treatment (e.g., electron beam, ultraviolet light, heat, or the like) from the viewpoint of improving heat resistance, strength, carbonization yield, shape stability, or moisture resistance, as long as the stretchability of the carbon material precursor is not significantly impaired.

[0086] (2.2) Carbonization process In the carbonization process, the flame-resistant material is carbonized to obtain a carbon material.

[0087] The carbonization method may be a method in which the flame-resistant material is subjected to a heat treatment in an atmosphere of an inert gas (eg, nitrogen, argon, helium, etc.) at a temperature higher than that in the flame-resistant treatment. The maximum heating temperature in the carbonization treatment is preferably 500°C or higher, more preferably 1000°C or higher, even more preferably 1100°C or higher, particularly preferably 1200°C or higher, and most preferably 1300°C or higher. The upper limit of the maximum heating temperature is preferably 3000° C. or less, and more preferably 2500° C. or less. The maximum heating temperature in the carbonization treatment is preferably 500°C to 3000°C.

[0088] The heating time at the maximum temperature in the carbonization treatment is not particularly limited, but is preferably from 30 seconds to 60 minutes, and more preferably from 1 minute to 30 minutes.

[0089] In the present disclosure, the "carbonization treatment" may include "graphitization" which is generally carried out by heating at a temperature of 2000°C to 3000°C in an inert gas atmosphere. The carbonization process may include multiple heat treatments. For example, a heat treatment (preliminary carbonization treatment) can be first performed at a temperature less than 1000°C, then a heat treatment (carbonization treatment) can be performed at a temperature of 1000°C or higher, and finally a heat treatment (graphitization treatment) can be performed at a temperature of 2000°C or higher. EXAMPLES

[0090] The above embodiment will be specifically described below with reference to examples, but the above embodiment is not limited to these examples.

[0091] [1] Preparation of acrylamide copolymers An aqueous solution was obtained by dissolving 100 parts by mass of a monomer consisting of 60 mol% acrylamide (AM), 35 mol% acrylonitrile (AN) and 5 mol% acrylic acid (AA) (anionic vinyl monomer) and 5 parts by mass of tetramethylethylenediamine in 400 parts by mass of ion-exchanged water. 4 parts by mass of ammonium persulfate were added to the obtained aqueous solution while stirring under a nitrogen atmosphere, and then the solution was heated at 80°C for 150 minutes to polymerize. The obtained aqueous solution was dropped into methanol to precipitate a copolymer, which was then collected and vacuum-dried at 80°C for 12 hours. As a result, a water-soluble AM / AN / AA (60 mol% / 35 mol% / 5 mol%) copolymer (acrylamide copolymer) was obtained.

[0092] [2] Examples and Comparative Examples [2.1] Comparative Example 1 100 parts by mass of an acrylamide copolymer and 3.52 parts by mass of monoammonium phosphate were dissolved and dispersed in ion-exchanged water to obtain a composition for producing a carbon material precursor. The obtained composition for producing a carbon material precursor was dried on a polytetrafluoroethylene petri dish. As a result, a film sample of the carbon material precursor with a thickness of about 0.1 mm was produced.

[0093] [2.2] Example 1 100 parts by mass of an acrylamide copolymer, 3.52 parts by mass of monoammonium phosphate, and 3.42 parts by mass of calcium chloride (1.23 parts by mass as calcium ions) were dissolved and dispersed in ion-exchanged water to obtain a composition for producing a carbon material precursor. The obtained composition for producing a carbon material precursor was dried on a polytetrafluoroethylene petri dish. As a result, a film sample of the carbon material precursor with a thickness of about 0.1 mm was produced.

[0094] [2.3] Example 2 A film sample was prepared in the same manner as in Example 1, except that calcium chloride was changed to 1.14 parts by mass of calcium hydroxide (0.62 parts by mass as calcium ions).

[0095] [2.4] Example 3 A film sample was prepared in the same manner as in Example 2, except that monoammonium phosphate was changed to 3 parts by mass of phosphoric acid.

[0096] [2.5] Example 4 A film sample was prepared in the same manner as in Example 1, except that the amount of calcium chloride added was changed to 8.56 parts by mass (3.08 parts by mass as calcium ions).

[0097] [2.6] Example 5 A film sample was prepared in the same manner as in Example 1, except that the amount of calcium chloride added was changed to 13.70 parts by mass (4.93 parts by mass as calcium ions).

[0098] [2.7] Example 6 100 parts by mass of an acrylamide copolymer, 3.52 parts by mass of monoammonium phosphate, 3.42 parts by mass of calcium chloride (1.23 parts by mass as calcium ion), and cellulose-derived biomass fiber "WFo-10002" (manufactured by Sugino Machine Co., Ltd., 2 mass% water dispersion, average fiber diameter 10-50 nm, polymerization degree 650) were dissolved and dispersed in ion-exchanged water to obtain a composition for producing a carbon material precursor. The obtained composition for producing a carbon material precursor was dried on a polytetrafluoroethylene petri dish. As a result, a film sample of the carbon material precursor with a thickness of about 0.1 mm was produced.

[0099] [2.8] Example 7 A film sample was prepared in the same manner as in Example 6, except that the amount of calcium chloride was changed to 1.71 parts by mass (0.62 parts by mass as calcium ions).

[0100] [2.9] Example 8 A film sample was produced in the same manner as in Example 6, except that the biomass fiber was changed to "AFo-10002" (manufactured by Sugino Machine Ltd., 2 mass% aqueous dispersion, average fiber diameter 10 to 50 nm, degree of polymerization 200).

[0101] [2.10] Example 9 A film sample was prepared in the same manner as in Example 1, except that monoammonium phosphate was not added.

[0102] [2.11] Example 10 A film sample was prepared in the same manner as in the example, except that monoammonium phosphate was not added.

[0103] [2.12] Example 11 A film sample was prepared in the same manner as in Example 1, except that calcium chloride was changed to 1.80 parts by mass of sodium chloride (0.71 parts by mass as sodium ion).

[0104] [2.13] Example 12 A film sample was prepared in the same manner as in Example 1, except that calcium chloride was changed to 2.94 parts by mass of magnesium chloride (0.75 parts by mass as magnesium ions).

[0105] [2.14] Example 13 A film sample was prepared in the same manner as in Example 1, except that calcium chloride was changed to 4.89 parts by mass of strontium chloride (2.70 parts by mass as strontium ions).

[0106] [2.15] Example 14 A film sample was prepared in the same manner as in Example 1, except that calcium chloride was changed to 5.44 parts by mass of calcium acetate monohydrate (1.23 parts by mass as calcium ions).

[0107] [3] Evaluation The film samples (carbon material precursors) of Examples 1 to 14 and Comparative Example 1 were subjected to the following evaluation tests.

[0108] [3.1] Storage modulus of carbon material precursor A film sample of the carbon material precursor was processed into a strip of 4 mm width and 30 mm length to prepare a sample. Using the sample, viscoelasticity measurement was carried out using a horizontal dynamic viscoelasticity measuring device (IT Measurement and Control Co., Ltd., DVA-220). The measurement conditions for the viscoelasticity measurement were as follows. From the measurement data, the storage modulus at each temperature is shown in Table 1. It is preferable that the storage modulus at 200°C is 10 MPa or more.

[0109] [3.1.1] Measurement conditions for viscoelasticity measurement Temperature conditions: normal temperature (25℃)~300℃ Temperature rise condition: 10℃ / min Data capture interval: 1℃ Frequency: 1Hz Distortion: 0.05% Static dynamic ratio: 2.5 Chuck distance: 20mm

[0110] [3.2] Evaluation of sagging of carbon material precursor [3.2.1] Length L The state of the sample after the above viscoelasticity measurement was observed to evaluate the state of sagging. As shown in Figure 1, the length (L) of the straight line connecting the chucks 10 of the dynamic viscoelasticity measuring device and the bottom side of the sample 20 was measured. The measurement results of the length (L) are shown in Table 1. It is preferable that the length (L) is less than 2 mm.

[0111] [3.2.2] Chuck Distance Change Rate The rate of change in the chuck distance was calculated from the following formula (1). The calculation results are shown in Table 1. In principle, when sagging occurs, the chuck distance becomes shorter and the rate of change in the chuck distance becomes negative. Exceptionally, there are cases where the contraction of the carbon material precursor is large and the chuck distance becomes shorter.

[0112] Formula (1): Chuck distance change rate [%] = 100 × [(Chuck distance after test – initial chuck distance) / initial chuck distance]

[0113] [3.3] Fusion evaluation [3.3.1] Evaluation of adhesion of carbon material precursor (without oil) Two film samples of the carbon material precursor were placed on top of each other on a hot plate. After the set temperature of the hot plate was raised from room temperature to 200°C, it was checked with tweezers whether the film samples could be peeled off from each other on the hot plate. After that, the set temperature of the hot plate was raised in increments of 25°C up to 300°C, and it was checked with tweezers whether the film samples could be peeled off from each other on the hot plate. The evaluation results were shown according to the following indexes.

[0114] [3.3.1.1] Evaluation criteria for fusion evaluation (without oil) A: There was almost no adhesion between the film samples, and they could be peeled off. B: The film samples were stuck to each other, but could be peeled off. C: It was possible to peel it off at 200℃, but it could not be peeled off at all between 225℃ and 300℃. D: At 200℃, peeling was completely prevented.

[0115] [3.3.2] Evaluation of adhesion of carbon material precursor (with oil) Silicone oil (KF-96-100cs, manufactured by Shin-Etsu Chemical Co., Ltd., no reactive functional group) was applied to one side of a film sample of a carbon material precursor using a cotton swab (A3D-100, industrial cotton swab, manufactured by Nippon Cotton Swab Co., Ltd.). Two film samples were placed on top of each other so that the surfaces coated with the silicone oil were in contact with each other, and the samples were placed on a hot plate. After the set temperature of the hot plate was raised from room temperature to 200°C, it was checked with tweezers whether the film samples peeled off each other on the hot plate. After that, the set temperature of the hot plate was raised by 25°C at a time up to 300°C, and it was checked with tweezers whether the film samples peeled off each other on the hot plate. The evaluation results were shown according to the following indexes.

[0116] [3.3.2.1] Evaluation criteria for fusion evaluation (with oil) A: There was almost no adhesion between the film samples, and they could be peeled off. B: The film samples were stuck to each other, but could be peeled off. C: It was possible to peel it off at 200℃, but it could not be peeled off at all between 225℃ and 300℃. D: At 200℃, peeling was completely prevented.

[0117] [3.4] Flame-resistant yield and carbonization yield of carbon material precursor Carbonization evaluation was performed using a differential thermobalance (Rigaku, ThermoPlusEV02). A Pt pan containing a cut-out film sample (approximately 1mg to 2mg) was set in the ThermoPlusEV02, and flame retardation was performed in air at 350°C for 10 minutes (heated from room temperature to 350°C at 10°C / min, then held at 350°C for 10 minutes). After that, the flame retarded sample was left in the Pt (platinum) pan and carbonized in nitrogen at 20°C / min up to 1200°C, while the mass was measured. The flame retardation yield was calculated from the measured mass using the following formula (2), and the carbonization yield was calculated using formula (3). The calculated results of the flame retardation yield and carbonization yield are shown in Table 1.

[0118] Equation (2): Flame retardant yield [%] = 100 × mass of film sample after flame retardant treatment / mass of film sample at 150°C during heating in flame retardant treatment Equation (3): Carbonization yield [%] = 100 × mass of film sample at each carbonization temperature / mass of film sample after flame retardation

[0119] Since acrylamide copolymers easily absorb water, the flame retardant yield was calculated based on the mass of the film sample at 150°C, when it is assumed that all water has evaporated. After flame retardant treatment, the film becomes less likely to absorb water, so the carbonization yield was calculated based on the mass of the film sample after flame retardant treatment.

[0120] [Table 1]

[0121] In Table 1, "PA" stands for monoammonium phosphate. "P" stands for phosphoric acid.

[0122] In the viscoelasticity measurement, in Comparative Example 1, the storage modulus was 5 MPa or less after 200°C, and 7 mm of sagging was confirmed (the sagging narrowed the gap between the chucks, so the rate of change in the gap between the chucks dropped significantly). In Example 1, the storage modulus was maintained at 10 MPa or more in the range of 160°C to 300°C, and no sagging occurred (the sample stretched a little, so the rate of change in the gap between the chucks increased a little). In Examples 2 to 5, the cationic metal content was adjusted, and the storage modulus tended to increase as the cationic metal content increased. No difference was observed in sagging or chuck distance, and no sagging occurred even when the cationic metal content was 0.62 parts by mass. In Examples 6 to 8, when biomass fiber was additionally added, the storage modulus was further increased. In Example 9, when no additive was used, the storage modulus at 200°C was higher but the storage modulus at 250°C was lower compared to Example 1. On the other hand, the storage modulus at 300°C was higher and no sagging occurred. In Example 10, when no additive was used in the system to which biomass fiber was added, the storage modulus at 250°C was lower but the storage modulus at 300°C was higher and no sagging occurred compared to Example 8. In Examples 11 to 13, the type and content of the cationic metal were adjusted. In Example 11, which used Na, a monovalent cationic metal, the storage modulus was lower than that of Example 2, which had a similar content of cationic metal, but the storage modulus was higher than that of Comparative Example 1, and no sagging occurred. In Example 12, which used Mg, a divalent cationic metal like Ca, the storage modulus was slightly lower than that of Example 2, which had a similar amount of cationic metal added, but was higher than that of Comparative Example 1, and no sagging occurred. In Example 13, which used Sr, a divalent cationic metal like Ca, the storage modulus was lower than that of Example 4, which had a similar amount of cationic metal added, but maintained 10 MPa or more in the range of 160°C to 300°C, and no sagging occurred. In Example 14, when calcium acetate monohydrate, an organic salt, was used as the cationic metal source instead of an inorganic salt, the storage modulus was equivalent to that of Example 1, and no sagging occurred. From the above results, it is clear that the inclusion of cationic metals suppresses the sagging of the carbon material precursor. Furthermore, it is presumed that the improved storage modulus allows high tension to be applied during stretching and flame-stabilization.

[0123] In the fusion evaluation, in Comparative Example 1, regardless of whether oil was present or absent, the evaluation result was "D" and the fusion occurred at 200°C. In Example 1, without oil, the evaluation result was "B". Furthermore, with oil, the adhesion was also reduced, so the evaluation result was "A". In Examples 2 and 3, which contained less cationic metal than Example 1, the evaluation result was "C" without oil, but was "B" with oil. In Examples 4 and 5, which contained more oil than Example 1, the evaluation results were the same as Example 1. In Examples 6 to 8, when biomass fiber was additionally added, the evaluation results were the same as in Example 1. In Example 9, when no additive was used, the evaluation result was "C" without oil, but when oil was used, the evaluation result was "B." In Example 10, when no additive was used in the system to which biomass fiber was added, the evaluation result was the same as in Examples 1 and 8, so it is presumed that fusion became difficult due to the synergistic effect of the cationic metal and biomass fiber. In Example 11, in which Na, a monovalent cationic metal, was used, the evaluation result was "C" regardless of whether an oil agent was used or not. In Example 12, in which Mg, a divalent cationic metal like Ca, was used, the evaluation result was "C" when there was no oil agent, but the evaluation result was "B" when there was oil agent, which was the same evaluation result as in Example 2. In Example 13, in which Sr, a divalent cationic metal like Ca, was used, the evaluation result was "B" when there was no oil agent, and the evaluation result was "A" when there was oil agent, which was the same result as in Example 4. In Example 14, calcium acetate monohydrate, which is an organic salt, was used as the cationic metal source instead of an inorganic salt, and the evaluation results were similar to those of Example 1. From the above results, it can be seen that the addition of cationic metals suppresses the fusion of the carbon material precursor. Note that the carbon material precursor derived from an acrylamide copolymer undergoes flame retardation at around 300°C, forming a ring structure and becoming infusible, so fusion is similarly suppressed even at temperatures above 300°C. For the same reasons as above, it is presumed that sagging is further suppressed at temperatures above 300°C.

[0124] Regarding the oxidation yield and carbonization yield, in Examples 1 to 14, oxidation yields and carbonization yields equal to or greater than those in Comparative Example 1 were obtained.

[0125] The following is further disclosed regarding the above embodiment.

[0126] A carbon material precursor according to a first embodiment includes an acrylamide copolymer and a cationic metal, and the acrylamide copolymer includes at least one type of structural unit derived from a vinyl monomer having an anionic functional group.

[0127] A second embodiment of the carbon material precursor is the first embodiment of the carbon material precursor, in which the valence of the cationic metal is divalent or greater.

[0128] A third aspect of the carbon material precursor is the carbon material precursor of the first or second aspect, in which the content of the cationic metal is 0.1 to 10 parts by mass with respect to 100 parts by mass of the acrylamide-based copolymer.

[0129] The carbon material precursor of a fourth aspect is the carbon material precursor of any one of the first to third aspects, in which the total content of constituent units derived from the vinyl monomer having the anionic functional group is 0.1 mol % to 50 mol % relative to the total amount of constituent units of the acrylamide copolymer.

[0130] A fifth aspect of the carbon material precursor is the carbon material precursor according to any one of the first to fourth aspects, in which the anionic functional group is a carboxy group.

[0131] A carbon material precursor according to a sixth aspect is the carbon material precursor according to any one of the first to fifth aspects, further comprising biomass fibers.

[0132] A seventh aspect of the carbon material precursor is the carbon material precursor of the sixth aspect, in which the biomass fiber includes fiber derived from at least one selected from the group consisting of cellulose and nitrogen-containing polysaccharide polymers.

[0133] The method for producing a carbon material according to an eighth embodiment includes: subjecting a carbon material precursor according to any one of the first to seventh embodiments to a flame-retardant treatment to obtain a flame-retardant material; and subjecting the flame-retardant material to a carbonization treatment. [Explanation of symbols]

[0134] 10: chuck of dynamic viscoelasticity measuring device, 20: sample

Claims

1. The present invention includes an acrylamide copolymer and a cationic metal, The carbon material precursor, wherein the acrylamide copolymer contains at least one type of structural unit derived from a vinyl monomer having an anionic functional group.

2. The carbon material precursor according to claim 1 , wherein the valence of the cationic metal is divalent or greater.

3. 3. The carbon material precursor according to claim 2, wherein the content of the cationic metal is 0.1 parts by mass to 10 parts by mass with respect to 100 parts by mass of the acrylamide-based copolymer.

4. 4. The carbon material precursor according to claim 3, wherein a content of the constituent units derived from the vinyl monomer having an anionic functional group is 0.1 mol % to 50 mol % relative to a total amount of the constituent units of the acrylamide copolymer.

5. The carbon material precursor according to claim 4 , wherein the anionic functional group is a carboxy group.

6. The carbon material precursor of claim 4 , further comprising biomass fibers.

7. The carbon material precursor according to claim 6 , wherein the biomass fibers include fibers derived from at least one selected from the group consisting of cellulose and nitrogen-containing polysaccharide polymers.

8. A method for producing a carbon material precursor according to claim 2, comprising the steps of: subjecting the carbon material precursor according to claim 2 to a flame-retardant treatment to obtain a flame-retardant product; subjecting the flame-retardant material to a carbonization treatment; A method for producing a carbon material, comprising:

Citation Information

Patent Citations

  • Silicone oil for fiber of carbon fiber precursor, fiber of carbon fiber precursor, flame resistant fiber, carbon fiber and method for producing the same

    JP2006183159A

  • Precursor fiber for carbon fiber, carbon fiber and method for producing thereof

    JP2008202208A

  • Carbon material precursor, carbon material precursor composition containing the same, and manufacturing method of carbon material using the same

    JP2019026827A

  • Carbon material precursor, carbon material precursor composition containing the same, and method for producing carbon material using these

    JP2019167516A

  • Carbon material precursor composition, method for producing same, and method for producing carbon material using same

    JP2019172800A

Cited By

  • Carbon fiber bundle, method for producing same, and carbon fiber precursor bundle

    WO2026048691A1